FLNC pathogenic variants in patients with cardiomyopathies: Prevalence and genotype‐phenotype correlations. Issue 4 (18th July 2019) - Ader, Flavie; De Groote, Pascal; Réant, Patricia; Rooryck‐Thambo, Caroline; Dupin‐Deguine, Delphine; Rambaud, Caroline; Khraiche, Diala; Perret, Claire; Pruny, Jean François; Mathieu‐Dramard, Michèle; Gérard, Marion; Troadec, Yann; et al.
Abstract: Pathogenic variants in FLNC encoding filamin C have been firstly reported to cause myopathies, and were recently linked to isolated cardiac phenotypes. Our aim was to estimate the prevalence of FLNC pathogenic variants in subtypes of cardiomyopathies and to study the relations between phenotype and genotype. DNAs from a cohort of 1150 unrelated index‐patients with isolated cardiomyopathy (700 hypertrophic, 300 dilated, 50 restrictive cardiomyopathies, and 100 left ventricle non‐compactions) have been sequenced on a custom panel of 51 cardiomyopathy disease‐causing genes. An FLNC pathogenic variant was identified in 28 patients corresponding to a prevalence ranging from 1% to 8% depending on the cardiomyopathy subtype. Truncating variants were always identified in patients with dilated cardiomyopathy, while missense or in‐frame indel variants were found in other phenotypes. A personal or family history of sudden cardiac death (SCD) was significantly higher in patients with truncating variants than in patients carrying missense variants ( P = .01). This work reported the first observation of a left ventricular non‐compaction associated with a unique probably causal variant in FLNC which highlights the role of FLNC in cardiomyopathies. A correlation between the nature of the variant and the cardiomyopathy subtype was observed as well as with SCD risk. Abstract :